PENGARUH CAPITAL INTENSITY, PERTUMBUHAN PENJUALAN DAN KINERJA KEUANGAN TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PERUSAHAAN TRANSPORTATION DAN LOGISTIC YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019 - 2023) - Aryani, Velia; Yazid, Abu (Jurnal Nusa Akuntansi, 2025)
This study aims to find out and obtain empirical evidence of the influence of capital intensity, sales growth and financial performance on tax avoidance in Transpotation and Logistics companies listed on the Indonesia Stock Exchange in 2019-2023. This type of research is quantitative research and uses secondary data in the form of annual financial statements on the official website of the Indonesia Stock Exchange (IDX) and the company's official website. The population in this study is 37 Transportation and Logistics companies listed on the Indonesia Stock Exchange in 2019-2023 and the sample technique was taken using purposive sampling by meeting the criteria of 6 companies that were sampled in 5 years of observation. The data analysis technique in this study uses panel data analysis using the help of e-views software version 12. The results of this study show simultaneously that capital intensity, sales growth and financial performance affects tax avoidance. And it partially shows that capital intensity has a significant effect on tax avoidance, while sales growth and financial performance have no significant effect on tax avoidance.